Analysis of mean maximal power in cycling with a modified critical power model allowing for a non-constant anaerobic work capacity - Dauwe, C.; Strobbe, S. (Journal of Science and Cycling, 2015)
Introduction: Since its introduction by Monod and Sherrer1 the Critical Power model has been applied to the analysis of cycling performances. In this model the Critical Power CP is the highest power that can be sustained without fatigue, and the total amount of work that can be produced until fatigue at any level above CP is indicated as the anaerobic work capacity W`. As yet W` is considered to be a constant quantity. However Mean Maximal Power data, indicated by MMP, or a (tlim,Plim) data set can by described adequately by this CP-model only in a limited time range, typically between tlim=20` and tlim=60`. Although the model can also formally be applied to short efforts, the relevant parameters CP and W` as obtained from short and long efforts will differ significantly. Therefore we propose a modified CP-W` model that will describe the MMP curve for the full relevant time range.